STRATEGI PENULISAN LEAD BERITA KRIMINAL DI SURAT KABAR RIAU POS - Harla Nursyahra; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The most important thing to consider in making a criminal news is packing leads that describe events that are interesting and capable of bewitching the reader. It should be applied because the interesting leads will determine the reader in making the decision to read a criminal news until it runs out or not, the more interesting a crime news lead to eat the greater the possibility of the news will be read to the end. In packing leads in the Riau Pos newspaper, in addition to reporters responsible for coverage have full authority over leads, the responsible reporters have the right to change, add and reduce leads that have been made by journalists. This study aims to find out how the strategy of writing crime news headlines in Riau Pos newspaper, the characteristics of crime news in Riau Pos newspaper, and the obstacles experienced by criminal journalists Riau Pos in packing crime news headlines.This research uses qualitative research type with explorative approach. Subjects in this study were criminal journalists and responsible for coverage in Riau Pos newspaper, selected subjects were those who were responsible for the publication of criminal news in Riau Pos newspaper. This study uses data collection techniques through interviews, observation, and documentation. To achieve the validity of dta in this study, the authors use extension of participation and triangulation.The result of the research shows that first, Riau Pos newspaper strategy in making crime news lead is to master the content of the subject matter, to determine which way criminal news will be made, to find the cause of the problem from the criminal occurrence, to describe the atmosphere of the location, using the sentence that tells, By journalists, using the acting lead functionality and must have interesting indications, stimulate the reader, and be presented with an easy-to-understand language. Secondly, the characteristics of crime news in Riau Pos are made by writing correct and semi-feature leads, containing the headline, and containing new events and events. Third, the obstacles experienced by journalists to make interesting criminal news leads is the limited time that criminal journalists have, as well as the amount of criminal news that must be paid per day perceived enough to burden the journalistKeywords: Lead , criminal news, writing strategy